An approach to the history of problem-based learning in the global context - Ortiz Ramos, Manuel Iván (SATHIRI, 2020)
Studying the problem as a stimulus of the teaching-learning process allows to compile and organize a historical framework supported by investigations of documents published by professors in research centers of different geopolitical contexts at a global level that consolidate the PBL, as a didactic method that uses the problem as a center for the construction of useful and meaningful knowledge where Students are the main protagonists because they develop their intelligence and critical thinking skills. This is a bibliometric study that used variables such as authors, institutions that in time and space saw in the PBL their emancipation and evolution from active teaching different from traditional passive learning techniques in university classrooms. Its antecedents were organized chronologically from its origins from the middle of the 20th century and its emancipation in the 21st century developing a dynamic, efficient and effective higher degree thinking. The results confirmed that its implementation provokes, motivates and challenges students to satisfy their cognitive needs by studying everyday problems in a globalized world, complex and rich in new knowledge to learn, based on changing realities.